Molecular sieve SSZ-113 with high acidity, synthesis and use thereof
By using boron pathway and aluminum replacement technology in the aluminum germanium silicate SSZ-113 molecular sieve, the problems of acid site loss and amorphous phase of existing zeolite materials were solved, and the synthesis of acid-rich SSZ-113 molecular sieve was achieved, improving the improvement of acid-rich SSZ-113 molecular sieve Catalytic performance and reaction efficiency are achieved.
Patent Information
- Application Number
- CN202380043816.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing zeolite materials have acid site loss and amorphous phase problems in catalytic organic compound conversion reactions, resulting in poor catalytic performance and lack of a novel molecular sieve structure with increased acid sites.
Aluminum germanium silicate SSZ-113 molecular sieve was synthesized by using 1,3-bis(2,3-dimethyl-1H-imidazolium)propane bication as structural guides, and aluminum was used to replace the skeleton. Boron increases its acid site and forms an acid-rich SSZ-113 molecular sieve.
Relatively more acid sites are achieved, the catalytic characteristics of the molecular sieve are improved, the efficiency and product purity of the catalytic organic compound conversion reaction are improved, and the acid site loss is avoided. The molecular sieve has increased acidity and catalytic properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 365,515, filed on May 31, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present invention relates to a novel synthetic crystalline molecular sieve having increased acidity, designated SSZ-113, and its synthesis. Background Art
[0004] Zeolite materials are known to have utility as adsorbents and to have catalytic properties for various types of organic compound conversion reactions. Certain zeolite materials are ordered porous crystalline materials having a well-defined crystalline structure determined by X-ray diffraction in which there are a large number of small cavities that may be interconnected by a number of smaller channels or pores. The size of these cavities and pores is uniform in a particular zeolite material. Because the size of these pores may allow the acceptance of adsorbed molecules of certain sizes while rejecting those of larger sizes, these materials are referred to as "molecular sieves," and these properties are exploited in various ways.
[0005] There are more than 250 known zeolite framework structures currently approved by the International Zeolite Association. In order to improve the performance of many organic compound conversions and adsorption processes, it is necessary to have new structures with properties different from known materials. Each structure has unique holes, channels and cage sizes, which give it specific properties as described above. Each structure also has a specific composition. Improvements in preparing purer single-phase materials are always important. Molecular sieves with increased acid sites are provided and can be valuable in catalyzing organic compound conversion reactions. Summary of the invention
[0006] According to the present invention, 1,3-bis(2,3-dimethyl-1 H A novel molecular sieve structure called SSZ-113 with increased acid sites was synthesized using a di-imidazolium) propane dication as a structure directing agent. The synthesis was carried out via a boron pathway. The final molecular sieve contains some boron in its framework. In one embodiment, the amount of boron may be 50-250 ppm.
[0007] The aluminogermanosilicate SSZ-113 molecular sieve of the present invention has increased acid sites, and thus increased acidity, and may have a chemical composition comprising the following molar relationship.
[0008] The prepared SSZ-113 molecular sieve also has increased acid sites and some boron in the framework.
[0009] The boron route involves preparing a boron SSZ-113 molecular sieve, which is a borogermanosilicate molecular sieve that is then treated to replace the boron in the framework with aluminum, thus producing a SSZ-113 molecular sieve with increased acid sites.
[0010] In another embodiment, a method for synthesizing a molecular sieve having increased acidity as described herein is provided, the method comprising: (a) providing a reaction mixture comprising: (1) a germanium oxide source; (2) a silicon oxide source; (3) a boron source; (4) 1,3-bis(2,3-dimethyl-1 H -imidazolium) propane dication source; (5) fluoride ion source; and (6) water; and (b) subjecting the reaction mixture to crystallization conditions sufficient to form boron molecular sieve crystals. The boron-containing SSZ-113 molecular sieve is then treated to remove SDA and subsequently treated to replace some or all of the boron with aluminum. SSZ-113 with increased acid sites is obtained.
[0011] In yet another aspect, a method of converting a feedstock comprising an organic compound to a conversion product is provided, the method comprising contacting the feedstock under organic compound conversion conditions with a catalyst comprising the SSZ-113 molecular sieve described herein in active form having increased acid sites.
[0012] Among other factors, the method of the present invention allows to obtain SSZ-113 molecular sieves with increased acid sites, i.e., the SSZ-113 is acid-rich or has increased acidity. By increased acid sites, it is meant that by using the method of the present invention and its boron path, SSZ-113 molecular sieves can be obtained, the acid sites of which are more than the possible acid sites of molecular sieves with aluminum sites and no boron sites prepared by conventional direct methods. When conventional routes are adopted, it has been found that some amorphous phases appear, so the loss of Al acid sites occurs. It has been quite surprisingly found that by first embedding boron into the framework, and then replacing boron with aluminum, SSZ-113 molecular sieves with a relatively increased number of acid sites can be obtained. The increased acid sites can lead to improvements in the catalytic properties of the SSZ-113 molecular sieves of the present invention. The SSZ-113 molecular sieve of the present invention also contains some boron. DETAILED DESCRIPTION
[0013] Overview
[0014] The term "aluminogermanosilicate" refers to a crystalline microporous solid comprising aluminum, germanium and silicon oxides in its framework structure. In some cases, one or more of these oxides may be replaced with other oxides.
[0015] The term "as synthesized" is used herein to refer to the form of the molecular sieve after its crystallization and before the removal of the organic structure directing agent.
[0016] The term "anhydrous" is used herein to refer to a molecular sieve that is substantially free of both physically adsorbed water and chemically adsorbed water.
[0017] As used herein, the numbering scheme for the Periodic Table Groups is as follows: Chem. Eng. News As disclosed in 1985, 63(5), 26-27.
[0018] By "increased" or "more" acid sites is meant that the SSZ-113 molecular sieve prepared by the method of the present invention contains more acid sites than possible acid sites of a molecular sieve conventionally prepared without the boron path of the present invention. When a conventional direct method using aluminum is adopted, it has been found that an amorphous phase occurs, which causes the loss of Al acid sites. It has been quite surprisingly found that by first embedding boron into the SSZ-113 framework, and then replacing boron with aluminum, a SSZ-113 molecular sieve is obtained, which has relatively more aluminic acid sites than the aluminic acid sites obtained if boron is not introduced in the initial preparation of the molecular sieve. Therefore, SSZ-113 is acid-rich or has an increased acidity. This increased acidity can affect and improve the catalytic properties of the molecular sieve. Molecular sieves are quite useful, for example, in converting a raw material containing an organic compound into a conversion product. Due to the boron path, some boron is still retained in the SSZ-113 molecular sieve.
[0019] Reaction mixture used in the synthesis of molecular sieves
[0020] The aluminum germanosilicate molecular sieve SSZ-113 of the present invention can be synthesized by the following boron route: (a) providing a reaction mixture, which comprises: (1) a germanium oxide source; (2) a silicon oxide source; (3) a boron source; (4) 1,3-bis(2,3-dimethyl-1 H -imidazolium) propane dication (Q) source; (5) fluoride ion source; and (6) water; and (b) subjecting the reaction mixture to crystallization conditions sufficient to form molecular sieve crystals. SDA can then be removed by calcination or ozone treatment. The calcined molecular sieve crystals (having boron in their framework) are then treated to replace at least most of the boron sites with aluminum, thereby providing a SSZ-113 molecular sieve with increased acid sites. Some boron is retained in the molecular sieve. Its amount is typically 50-250 ppm.
[0021] The reaction mixture used to form the boron SSZ-113 molecular sieve may have a composition expressed in molar ratios within the following ranges:
[0022] Table 1
[0023] Suitable germanium oxide sources include germanium oxide, germanium alkoxides (eg, germanium ethoxide), germanium hydroxides, and germanium carboxylates.
[0024] Suitable silica sources include colloidal silica, fumed silica, precipitated silica, alkali metal silicates and tetraalkyl orthosilicates. FAU framework type zeolites such as zeolite Y can also provide silica. The FAU zeolite will exhibit a SiO2 / Al2O3 molar ratio of at least 250, and in one embodiment at least 300, or a molar ratio of 300-500.
[0025] The molar ratio of Si:Ge may be at least 1:1 (eg, 2:1 to 500:1 or even 5:1 to 100:1). In one embodiment, the ratio may be 4 to 12, such as 6 to 10.
[0026] Suitable boron sources may include boric acid, which is preferred.
[0027] Additionally or alternatively, combined sources of silica and alumina may be used and may include an aluminosilicate zeolite (eg, zeolite Y) and a clay or treated clay (eg, metakaolin).
[0028] Conveniently, Q comprises 1,3-bis(2,3-dimethyl-1 H -imidazolium)propane dication:
[0029]
[0030] The above-mentioned diquaternary ammonium compounds can be easily synthesized by reacting 1,3-dihalopropane (e.g., 1,3-dibromopropane or 1,3-diiodopropane) with 1,2-dimethylimidazole by methods known in the art (see, e.g., SIZones et al., J.Mater. Chem. 2005, 15, 4215-4223).
[0031] Suitable sources of Q are hydroxides and / or other salts of diquaternary ammonium compounds, or mixtures thereof.
[0032] Suitable fluoride ion sources include hydrogen fluoride, ammonium fluoride and ammonium hydrogen difluoride.
[0033] The reaction mixture may contain seeds of boron SSZ-113 molecular sieve material, such as boron SSZ-113 from a previous synthesis, in an amount of 0.01 to 10000 ppm by weight (e.g., 100 to 5000 ppm by weight) of the reaction mixture. Seeding can be advantageous in reducing the amount of time required for complete crystallization to occur. In addition, seeding can result in an increase in the purity of the product obtained by promoting nucleation and / or formation of boron SSZ-113 on any undesirable phase.
[0034] For each embodiment described herein, the molecular sieve reaction mixture can be supplied from more than one source. Likewise, two or more reaction components can be supplied from one source.
[0035] The reaction mixture may be prepared batchwise or continuously. The crystal size, morphology and crystallization time of the molecular sieves described herein may vary depending on the nature of the reaction mixture and the crystallization conditions.
[0036] Crystallization and post-synthesis processing
[0037] Consistent with the boron route, crystallization of the molecular sieve from the above reaction mixture can be carried out in a suitable reactor vessel (such as a polypropylene tank or Teflon liner or stainless steel autoclave) under static, tumbling or stirring conditions at a temperature of 125° C. to 200° C. for a time sufficient for crystallization to occur at the temperature used (e.g., 2 to 20 days). Crystallization is typically carried out in a closed system under autogenous pressure.
[0038] Once the boron-containing molecular sieve crystals are formed, the solid product can be recovered from the reaction mixture by conventional mechanical separation techniques such as centrifugation or filtration. The crystals are washed with water and then dried to obtain the initially synthesized molecular sieve crystals. The drying step is usually carried out at a temperature below 200°C.
[0039] As a result of the crystallization process, the recovered crystallized molecular sieve product contains in its pore structure at least a portion of the organic structure directing agent used in its synthesis.The molecular sieves described herein may be subjected to subsequent treatment to remove some or all of the structure directing agent (Q) used in its synthesis.
[0040] Removal of the structure directing agent may be conveniently performed by heat treatment, wherein the as-synthesized material may be heated at a temperature of at least 370° C. for at least 1 minute and not longer than 24 hours. The heat treatment may be performed at a temperature of up to 925° C. Although subatmospheric and / or superatmospheric pressures may be used for the heat treatment, atmospheric pressure is generally desired for convenience.
[0041] Additionally or alternatively, the organic structure directing agent may be removed by ozone treatment (see, e.g., AN Parikh et al., Micropor. Mesopor. Mater. 2004, 76, 17-22). In one embodiment, treatment with ozone is preferred because it can provide a higher micropore volume.
[0042] The boron SSZ-113 molecular sieve crystals can then be treated to replace at least some of the boron with aluminum, although it is preferred to replace most (90%) of the boron, if not almost all of the boron. In one embodiment, the amount of boron remaining after the exchange can be in an amount of 50 to 250 ppm. Conventional techniques such as ion exchange can be used. However, treating the molecular sieve with an aqueous solution of aluminum nitrate is a preferred way to replace boron in the framework with aluminum. The treatment can be completed by contacting the molecular sieve with an aluminum nitrate solution under reflux.
[0043] SSZ-113 molecular sieves with increased acid sites, especially in their metal, hydrogen and ammonium forms, are particularly useful in catalyzing certain organic (e.g. hydrocarbon) conversion reactions. In the present invention, molecular sieves containing no organic matter in their hydrogen form, with or without metal functionalities, are referred to as "active form" molecular sieves.
[0044] Characterization of Molecular Sieve
[0045] The final acid-added molecular sieve SSZ-113 may have a chemical composition comprising the following molar relationship:
[0046] Table 2
[0047] The molecular sieve SSZ-113 of the present invention exhibits its characteristic XRD pattern, but it also has increased acid sites. Some residual boron is also retained in the structure. On the one hand, the molecular sieve of the present invention has a composition comprising the following molar relationship:
[0048] Al2O3:( n )(SiO2+GeO2)
[0049] wherein n≥20. In one embodiment, n in the aforementioned relationship is from 20 to 600.
[0050] The high acidity SSZ-113 molecular sieve obtained after the aluminum exchange procedure will have a powder XRD pattern comprising at least the peaks of Table 3, but wherein the molecular sieve also contains some boron and has increased acidity.
[0051] Table 3
[0052] Characteristic peaks of acid-added SSZ-113
[0053] (a) ±0.30 degrees
[0054] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0055] As will be appreciated by those skilled in the art, the determination of the parameter 2-theta (2θ) is subject to both human and mechanical error, the combination of which can impose an uncertainty of approximately ±0.30° on each reported 2-theta value. o) is recorded as the ratio of the peak intensity to the intensity of the strongest peak, which is assigned a value of 100. The relative intensities of the d-spacings are represented by the designations VS, S, M, and W, which represent very strong, strong, medium, and weak, respectively. In terms of relative intensity, the above designations are defined as: W (weak) <20; M (medium) is >20 and <40; S (strong) is >40 and <60; and VS (very strong) is >60. When the intensity is close to the end points of the range, the intensity can be characterized as being in any range. For example, an intensity of 18-22 can be listed as WM. However, due to the variation in the intensity of the lines, as is known in the art, one or more lines may have intensities that are in adjacent ranges.
[0056] The powder X-ray diffraction patterns presented herein were collected by conventional techniques. The radiation was CuKα radiation. The peak heights and positions as a function of 2θ (where θ is the Bragg angle) were read from the relative intensities of the peaks (adjusting for background), and d (corresponding to the inter-plane spacing of the recorded lines) was calculated.
[0057] Slight changes in the diffraction pattern can be attributed to changes in the molar ratio of the framework material of the sample, which is due to changes in the lattice constant. In addition, disordered materials and / or sufficiently small crystals will affect the shape and intensity of the peaks, resulting in significant peak broadening. Slight changes in the diffraction pattern can also be attributed to changes in the organic compounds used in the preparation. Calcination can also cause small shifts in the XRD pattern. Despite these minor perturbations, the basic lattice structure remains unchanged.
[0058] The increased acidity of a molecular sieve can be measured, for example, by measuring its Bronsted acidity.
[0059] Adsorption and catalysis
[0060] Molecular sieve SSZ-113 with increased acid sites can be used as an adsorbent or catalyst to catalyze a variety of organic compound conversion processes, including many current conversion processes of commercial / industrial importance. Examples of chemical conversion processes (which are effectively catalyzed by acid-rich SSZ-113 itself or in combination with one or more other catalytically active materials (including other crystalline catalysts and functional metals)) include those requiring catalysts or catalytic metals with acid activity. Examples of organic conversion processes that can be catalyzed by acid-rich SSZ-113 can include, for example, cracking, hydrocracking, disproportionation, alkylation, oligomerization and isomerization.
[0061] As in the case of many catalysts, it may be desirable to introduce additional materials that tolerate the temperature and other conditions used in organic conversion processes into SSZ-113 with increased acid sites. Such materials may include active and inactive materials and synthetic or naturally occurring zeolites and inorganic materials such as clays, silica and / or metal oxides such as alumina. The latter may be naturally occurring, or in the form of a gelatinous precipitate or gel, including a mixture of silica and metal oxides. The use of materials (which are active) in conjunction with acid-rich SSZ-113 (i.e., in combination with it or present during the synthesis of new materials) often can change the conversion rate and / or selectivity of the catalyst in certain organic conversion processes. Inactive materials may be suitable as diluents to control the amount of conversion in a given process, so that the product can be obtained in an economical and orderly manner without other means of controlling the reaction rate. These materials may be introduced into naturally occurring clays (e.g., bentonite and kaolin) to improve the crush strength of the catalyst under commercial operating conditions. These materials (i.e., clays, oxides, etc.) may serve as binders for catalysts. Providing a catalyst with good crush strength may be desirable because, in commercial use, it may be desirable to prevent the catalyst from breaking down into powdery material (fines).These clay and / or oxide binders are generally used for the sole purpose of improving the crush strength of the catalyst.
[0062] Naturally occurring clays that can be composited with acid-enriched SSZ-113 include the montmorillonite and kaolin families, which include subbentonites, and the commonly known kaolins such as Dixie, McNamee, Georgia and Florida clays or other clays in which the major mineral components are halloysite, kaolinite, dickite, nacrite or anthracite. Such clays can be used in a raw state, such as as originally mined, or they can have been initially subjected to calcination, acid treatment or chemical modification. Additionally or alternatively, binders useful for composites with acid-enriched SSZ-113 can include inorganic oxides such as silica, zirconium oxide, titanium oxide, magnesium oxide, beryllium oxide, aluminum oxide and mixtures thereof.
[0063] In addition to or as an alternative to the foregoing materials, the acid-rich SSZ-113 can be composited with porous matrix materials such as silica-alumina, silica-magnesia, silica-zirconia, silica-thoria, silica-beryllia, silica-titania, and ternary compositions such as silica-alumina-thoria, silica-alumina-zirconia, silica-alumina-magnesia, and silica-magnesia-zirconia.
[0064] The relative proportions of the SSZ-113 having increased acid sites and the inorganic oxide matrix can vary widely, with the SSZ-113 content ranging from 1 to 90 wt % (eg, 2 to 80 wt %) of the composite. Example
[0065] The following illustrative examples are intended to be non-limiting. Example 1
[0066] 5 mmol of SDA1,3-bis(2,3-dimethyl-1 H -imidazolium) propane dihydroxide solution. Then 0.54g of Tosoh HUA-390 FAU zeolite (SAR about 500), 0.10g of GeO2 and 0.06g of H3BO3 (boric acid) were added to the cup. After evaporation in a fume hood for a few days to reduce the H2O / TO2 ratio to 7, 0.20g of 50% HF was added to the reaction and then sealed and heated at 160°C for 7 days while rotating at 43 RPM. After cooling and collecting the sample by filtration and washing, the XRD data showed SSZ-113.
[0067] The as-made borogermanosilicate SSZ-113 can then be calcined in air at 540°C using a ramp program of 1°C to 120°C / min, hold in oven for 2 hours / ramp to 540°C at 1°C / min / hold for 4 hours and cool.
[0068] The XRD pattern was essentially unchanged.
[0069] Then Al was used to replace B. 0.26 g of calcined boron SSZ-113 was placed in a glass vial with 10 ml of water, and then 0.30 g of aluminum nitrate (nonahydrate) was added. The vial was closed and heated statically at 95°C for 2 days. After cooling, it was then filtered, then washed with HCl to pH = 2, and then washed with distilled water. The following table shows the changes in elemental analysis before and after calcination and aluminum nitrate treatment: Example 2
[0070] The acidity of the now treated Al-substituted B SSZ-113 of Example 1 was measured. The Bronsted acidity was determined by temperature programmed desorption (TPD) of n-propylamine adapted from the published descriptions of TJ GricusKofke et al. (J. Catal. 1988, 114, 34-45); TJ GricusKofke et al. (J. Catal. 1989, 115, 265-272); and JG Tittensor et al. (J. Catal. 1992, 138, 714-720). The samples were pretreated at 400° C.-500° C. in flowing dry H2 for 1 hour. The dehydrated samples were then cooled to 120° C. in flowing dry helium and held at 120° C. for 30 minutes in flowing helium saturated with n-propylamine for adsorption. The sample saturated with n-propylamine was then heated to 500°C at a rate of 10°C / min in flowing dry helium. The Bronsted acidity was calculated based on the weight loss versus temperature determined by thermogravimetric analysis (TGA) and the effluent NH3 and propylene determined by mass spectrometry. The material was found to have strong acid sites. The desorption data for the peak close to 400°C were converted to a measurement of 200 μmol amine / g.
[0071] As used herein, the words "comprising" are intended to be an open-ended transition, meaning the inclusion of the recited elements but not necessarily the exclusion of other unrecited elements. The phrase "consisting essentially of is intended to mean the exclusion of other elements having any critical importance to the composition. The phrase "consisting of is intended to be a transition, meaning the exclusion of all elements other than the recited elements, except for only trace amounts of impurities.
[0072] To the extent not inconsistent with this document, all patents and publications referenced herein are hereby incorporated by reference. It will be understood that some of the above-mentioned structures, functions, and operations of the above-mentioned embodiments are not necessary for practicing the present invention, and are included in the specification only for the completeness of exemplary embodiments or embodiments. In addition, it will be understood that the specific structures, functions, and operations set forth in the above-mentioned referenced patents and publications can be practiced in conjunction with the present invention, but they are not essential to its practice. Therefore, it should be understood that the present invention can be practiced as specifically described without actually departing from the spirit and scope of the present invention defined by the appended claims.
Claims
1. A molecular sieve having an X-ray diffraction pattern comprising the peaks listed in the following table: And wherein the molecular sieve comprises boron and has increased acid sites.
2. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: Al2O3:(n)(SiO2+GeO2) wherein n is at least 20.
3. The molecular sieve according to claim 1, having a composition comprising the following molar relationship: Al2O3:(n)(SiO2+GeO2) Where n is 20 to 600.
4. The molecular sieve according to claim 1, having a composition comprising the following molar relationship:
5. The molecular sieve according to claim 4, having a composition comprising the following molar relationship:
6. A method for synthesizing the molecular sieve of claim 1, the method comprising: (a) providing a reaction mixture comprising: (1) Germanium oxide source; (2) silicon oxide source; (3) Boron source; (4) 1,3-bis(2,3-dimethyl-1H-imidazolium)propane dication (Q) source; (5) a fluoride ion source; and (6) Water; (b) subjecting the reaction mixture to crystallization conditions sufficient to form boron-containing molecular sieve crystals; (c) removing at least some of Q; and (d) Some of the boron in the molecular sieve crystals of (c) is replaced by aluminum.
7. The method of claim 6, wherein the reaction mixture has the following composition expressed in molar ratio: 。 8. The method of claim 6, wherein the reaction mixture has the following composition expressed in molar ratio: 。 9. The method of claim 6, wherein the silicon oxide source comprises zeolite Y having a SiO2 / Al2O3 ratio of at least 300.
10. The method of claim 6, wherein the crystallization conditions comprise a temperature of 125°C to 200°C.
11. The method according to claim 6, wherein Q is removed by calcination.
12. The method of claim 6, wherein Q is removed by treatment with ozone.
13. The method of claim 6, wherein replacing boron with aluminum comprises refluxing the molecular sieve crystals with an aluminum nitrate solution.
14. A process for converting a feedstock comprising an organic compound into a conversion product, the process comprising contacting the feedstock with a catalyst comprising the molecular sieve of claim 1 in active form under organic compound conversion conditions.
15. SSZ-113 molecular sieve prepared by the method of claim 6.
16. SSZ-113 molecular sieve prepared by the method of claim 7.
